What Works in Readmissions Reduction: How Hospitals Improve Performance. - Brewster, Amanda L; Cherlin, Emily J; Ndumele, Chima D; Collins, Diane; Burgess, James F; Charns, Martin P; Bradley, Elizabeth H; Curry, Leslie A (Medical care, 2016)
Hospitals across the United States are pursuing strategies to reduce avoidable readmissions but the evidence on how best to accomplish this goal is mixed, with no specific clinical practice shown to reduce readmissions consistently. Changes to hospital organizational practices, a key component of context, also may be critical to improving performance on readmissions, but this has not been studied.